2004
DOI: 10.1111/j.1600-051x.2004.00476.x
|View full text |Cite
|
Sign up to set email alerts
|

Smoking cessation increases gingival blood flow and gingival crevicular fluid

Abstract: The results show that the gingival microcirculation recovers to normal in the early stages of smoking cessation, which could activate the gingival tissues metabolism/remodeling, and contribute to periodontal health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
92
0
7

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(105 citation statements)
references
References 41 publications
4
92
0
7
Order By: Relevance
“…Morozumi et al 63 and Nair et al 64 reported an increase in gingival blood flow after smoking cessation, as observed with Laser Doppler flowmetry.…”
Section: Smoking Cessation and Periodontal Tissuesmentioning
confidence: 89%
“…Morozumi et al 63 and Nair et al 64 reported an increase in gingival blood flow after smoking cessation, as observed with Laser Doppler flowmetry.…”
Section: Smoking Cessation and Periodontal Tissuesmentioning
confidence: 89%
“…In our study, the effect of smoking on periodontal destruction did not reach statistical significance in the T1DM group; however, in T2DM group smokers had a significantly lower mean BOP and percentage of CAL >5 mm. Lower levels of gingival bleeding could be explained by the vasoconstrictive effect of nicotine 32 . On the other hand, there were only 11 smokers (12.6%) among patients with T2DM in the present study and, therefore, a small number of the subjects may produce ambiguous results.…”
Section: Discussionmentioning
confidence: 99%
“…Observational and experimental studies have shown that cigarette smoking suppresses the gingival inflammatory response to a given amount of plaque as measured by bleeding on probing (Bergström & Flodérus-Myrhed 1983, Preber & Bergström 1985, Bergström 1990, Danielsen et al 1990, Lie et al 1998, Giannopoulou et al 2003a, Dietrich et al 2004). However, once cigarette smokers quit smoking, bleeding on probing that was not previously apparent can be found within weeks, even if plaque control has improved, suggesting a causal relationship (Nair et al 2003, Morozumi et al 2004). …”
Section: Tobacco Smoking and Gingival Inflammationmentioning
confidence: 99%